Measuring Peer Feedback on Writing Class: A Study on Third-Semester Pre-Service English Teachers - Didik Rinan Sumekto; Heny Setyawati (Lingua Cultura, 2019)
This research aimed to measure the contributions of students’ peer feedback set in the collaborative writing class. Of 144 population, 55 undergraduate English education students were involved as the participants in a quasi-experimental research design which was conducted through a non-randomized five experimental and five control groups. There were 25 experimental participants attended in the regular classes with the collaborative writing class syntax, namely; genres selection, problem-based learning, genres, and peer feedback practices, while other 30 control participants naturally attended in the same activity. Data were collected through the collaborative writing’s pre- and post-test, and peer feedback instruments within four weeks of the lectures. Data analysis used the Mann-Whitney U, and Wilcoxon signed rank tests. The findings show that the collaborative writing’s peer feedback positively contributes to students’ writing skills and learning awareness resulted in the post-tests. Peer feedback may correct students’ writing mistakes and contribute a significant difference between the experimental and control groups (Z=-2,471; p≤0,05). Peer feedback socially tightens students’ collaborative writing and promotes a mutual relationship among group members, and reduces lecturer’s feedback.